Antifouling porcelain insulator and preparation method thereof
By coating porcelain insulators with an antifouling agent composed of nanomaterials, combined with the effects of photocatalysts and antibacterial agents, the problems of traditional porcelain insulators being easy to pollute outdoors and having poor self-cleaning ability are solved, achieving higher antifouling performance and Self-cleaning ability extends service life.
Patent Information
- Application Number
- CN202411500558.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional porcelain insulators are easily contaminated in outdoor environments, resulting in a decrease in insulation performance, increasing the risk of flashover, and poor self-cleaning ability, making it difficult to adapt to high-temperature and high-humidity environments.
Antifouling agents using nano-silica, modified nano-titanium dioxide, silane coupling agents, antibacterial agents, thickeners and silicone resins are used to form an anti-fouling glaze layer through coating, combining the photocatalytic performance and The antibacterial effect of antibacterial agents improves the antifouling performance and self-cleaning ability of insulators.
It significantly improves the anti-fouling performance and self-cleaning ability of porcelain insulators, reduces the risk of pollution flashover, enhances mechanical performance and stability, extends service life, and provides reliable guarantee for the stable operation of the power system.
Smart Images

Figure BDA0005102474000000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-pollution of porcelain insulators, and in particular to an anti-pollution porcelain insulator and a preparation method thereof. Background Art
[0002] In power systems, porcelain insulators are widely used due to their excellent electrical properties and mechanical strength. However, they are easily contaminated in outdoor environments and covered with dust and dirt in wind and rain. In wet weather such as rain, snow, and fog, creepage and flashover may occur on the surface of ceramic insulators, and some may cause short circuit tripping. Major accidents may cause large-scale power grid paralysis. When traditional porcelain insulators are used outdoors, their surface easily absorbs dirt, resulting in reduced insulation performance:
[0003] (1) Surface pollution is easy to accumulate: The surface of traditional anti-pollution porcelain insulators is relatively rough, which easily absorbs pollutants such as dust and oil. In a humid environment, pollutants will form a conductive layer, reduce the insulation performance of the insulator, and increase the risk of flashover.
[0004] (2) Poor self-cleaning ability: General porcelain insulators lack an effective self-cleaning mechanism, and it is difficult to completely remove surface dirt by natural conditions (such as rainwater washing, etc.). Over time, the dirt accumulation will become more and more serious, affecting the normal operation of the insulator.
[0005] (3) Insufficient adaptability to special environments: In high temperature and high humidity environments, the anti-pollution effect of traditional anti-pollution porcelain insulators is limited, and flashover accidents are prone to occur. Summary of the invention
[0006] Based on this, the present invention proposes an anti-pollution porcelain insulator and a preparation method thereof, aiming to utilize the characteristics of nanomaterials to improve the anti-pollution performance of the porcelain insulator, extend its service life, and provide reliable guarantee for the safe and stable operation of the power system.
[0007] The technical solution of the present invention is achieved as follows: an anti-fouling porcelain insulator comprises a porcelain insulator substrate and an anti-fouling glaze layer, wherein the anti-fouling glaze layer is formed by coating the surface of the porcelain insulator substrate with an anti-fouling agent, wherein the anti-fouling agent comprises the following raw materials in parts by weight: 10-20 parts of nano silicon dioxide, 30-50 parts of photocatalyst, 1-5 parts of silane coupling agent, 1-5 parts of antibacterial agent, 2-8 parts of thickener, 5-20 parts of silicone resin, and 12-22 parts of organic solvent; the photocatalyst is modified nano titanium dioxide, the antibacterial agent is nano silver, alliin and cashew nut shell oil in a mass volume g / mL ratio of (5.5-9.5):(2.5-8.1):(1.2-3.8), and the thickener is xanthan gum or hydroxyethyl cellulose.
[0008] Furthermore, the antifouling agent comprises the following raw materials in parts by weight: 15 parts of nano-silicon dioxide, 40 parts of photocatalyst, 3 parts of silane coupling agent, 3 parts of antibacterial agent, 5 parts of thickener, 12 parts of silicone resin, and 17 parts of organic solvent.
[0009] Furthermore, the porcelain insulator matrix includes but is not limited to feldspar porcelain insulators, high-alumina porcelain insulators, alumina porcelain insulators, beryllium oxide porcelain insulators, mullite porcelain insulators, silicon carbide ceramic insulators or silicon nitride ceramic insulators.
[0010] Furthermore, the antifouling agent is coated on the surface of the porcelain insulator substrate to a thickness of 40-60 μm.
[0011] Furthermore, the silane coupling agent is selected from KH-560 or γ-aminopropyltriethoxysilane to enhance the adhesion of the coating.
[0012] Furthermore, the organic silicone resin is one or more combinations of methyl silicone resin, phenyl silicone resin and fluorosilicone resin.
[0013] Furthermore, the organic solvent is selected from xylene, ethanol, isopropanol, ethyl acetate or acetone.
[0014] Furthermore, a method for preparing an anti-pollution porcelain insulator comprises the following steps:
[0015] S1. Preparation of photocatalyst: dispersing nano-titanium dioxide in anhydrous ethanol, with the mass volume ratio of nano-titanium dioxide to anhydrous ethanol being 15-25:80 g / mL, to form a titanium dioxide suspension, adding a metal salt solution, stirring at a stirring speed of 1000-3000rpm and a temperature of 20-100°C for 30-70min, applying a pulsed magnetic field oscillation during the stirring process, with a pulsed magnetic field frequency of 8-12Hz, a pulsed magnetic field voltage of 120-180V, and a magnetic induction intensity of 1.2-2.5T, and calcining at 300-800°C for 2-6h to obtain modified nano-titanium dioxide, i.e., a photocatalyst; the crystal form and particle size of nano-titanium dioxide can be adjusted to improve its photocatalytic efficiency;
[0016] S2, preparing nano antifouling coating: stirring and mixing the photocatalyst, nano silicon dioxide, silane coupling agent, antibacterial agent, thickener, silicone resin and organic solvent to obtain nano antifouling coating;
[0017] S3, porcelain insulator substrate modification: the porcelain insulator substrate is cleaned and dried, coated with photoresist, and the desired pattern mask is formed by photolithography technology, and then immersed in an etchant, and immersed in an oscillation at 40-60°C for 40-90 minutes, with an oscillation frequency of 25-35KHz; the etchant includes but is not limited to hydrofluoric acid, nitric acid, hydrochloric acid or trimethylammonium hydroxide; the porcelain insulator substrate is formed into a micro-nano structure, and the surface tension and capillary action are used to promote the flow of rainwater on the surface and the removal of dirt;
[0018] S4, coating: coating the nano antifouling coating obtained in S2 onto the porcelain insulator substrate modified in S3 to obtain an antifouling porcelain insulator.
[0019] Furthermore, the metal salt solution in S1 is a sodium chloride solution, a potassium chloride solution, a ferric chloride solution or a silver nitrate solution with a mass concentration of 50-80%.
[0020] Furthermore, the coating of S4 is one of spraying, brushing or dipping.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) Improve anti-fouling performance and self-cleaning ability: The modified nano-titanium dioxide has efficient photocatalytic performance, which can decompose the dirt on the surface of the insulator under light, reduce the accumulation of dirt, reduce the risk of flashover, and achieve a self-cleaning effect; the antibacterial agent composed of nano-silver, alliin and cashew nut shell oil can effectively inhibit the growth of microorganisms such as bacteria and fungi, and prevent the influence of biological dirt on the performance of the insulator;
[0023] (2) Enhance mechanical properties and stability: Nano-silicon dioxide enhances the hardness and wear resistance of the anti-fouling glaze layer, improves the mechanical strength of the insulator, and extends its service life; silane coupling agents improve the bonding force between the components, improve the adhesion between the anti-fouling glaze layer and the porcelain insulator substrate, and prevent the glaze layer from falling off; thickeners adjust the viscosity of the coating to ensure the uniformity and stability of the coating process. The components work synergistically according to a specific ratio.
[0024] (3) Optimization of the preparation method: The preparation method includes the steps of preparing photocatalyst, preparing nano antifouling coating, modifying and coating the porcelain insulator matrix. During the stirring process, pulsed magnetic field oscillation is applied to promote the dispersion of nano titanium dioxide and the uniform doping with metal salts, thereby improving the modification effect; the porcelain insulator matrix modification improves the bonding force between the glaze layer and the matrix; these steps can ensure that the antifouling agent is evenly coated on the surface of the insulator to form a dense glaze layer, improve the antifouling performance and insulation performance of the insulator, and provide a reliable guarantee for the stable operation of the power system. DETAILED DESCRIPTION
[0025] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0026] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0027] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0028] Example 1
[0029] An anti-fouling porcelain insulator comprises a feldspar porcelain insulator substrate and an anti-fouling glaze layer, wherein the anti-fouling glaze layer is formed by coating an anti-fouling agent on the surface of the porcelain insulator substrate, and the coating thickness is 40 μm, and the anti-fouling agent comprises the following raw materials in parts by weight: 10 parts of nano silicon dioxide, 30 parts of photocatalyst, 1 part of silane coupling agent, 1 part of antibacterial agent, 2 parts of thickener, 5 parts of organic silicone resin, and 12 parts of organic solvent;
[0030] The photocatalyst is modified nano titanium dioxide;
[0031] The silane coupling agent is selected from KH-560;
[0032] The antimicrobial agent is nanosilver, alliin and cashew nut shell liquid in a mass volume g / mL ratio of 5.5:2.5:1.2;
[0033] The thickener is hydroxyethyl cellulose;
[0034] The organosilicon resin is methyl silicone resin;
[0035] The organic solvent is selected from xylene, ethanol, isopropanol, ethyl acetate or acetone.
[0036] Example 2
[0037] An anti-fouling porcelain insulator comprises an alumina porcelain insulator substrate and an anti-fouling glaze layer, wherein the anti-fouling glaze layer is formed by coating an anti-fouling agent on the surface of the porcelain insulator substrate, and the coating thickness is 60 μm, and the anti-fouling agent comprises the following raw materials in parts by weight: 20 parts of nano silicon dioxide, 50 parts of photocatalyst, 5 parts of silane coupling agent, 5 parts of antibacterial agent, 8 parts of thickener, 20 parts of organic silicone resin, and 22 parts of organic solvent;
[0038] The photocatalyst is modified nano titanium dioxide;
[0039] The silane coupling agent is selected from γ-aminopropyltriethoxysilane;
[0040] The antibacterial agent is nanosilver, alliin and cashew nut shell liquid in a mass volume g / mL ratio of 9.5:8.1:3.8;
[0041] The thickener is xanthan gum;
[0042] The organosilicon resin is a phenyl silicone resin;
[0043] The organic solvent is selected from xylene, ethanol, isopropanol, ethyl acetate or acetone.
[0044] Example 3
[0045] An anti-fouling porcelain insulator comprises a mullite porcelain insulator substrate and an anti-fouling glaze layer, wherein the anti-fouling glaze layer is formed by coating an anti-fouling agent on the surface of the porcelain insulator substrate, and the coating thickness is 50 μm, and the anti-fouling agent comprises the following raw materials in parts by weight: 15 parts of nano silicon dioxide, 40 parts of photocatalyst, 3 parts of silane coupling agent, 3 parts of antibacterial agent, 5 parts of thickener, 12 parts of silicone resin, and 17 parts of organic solvent;
[0046] The photocatalyst is modified nano titanium dioxide;
[0047] The silane coupling agent is selected from KH-560;
[0048] The antimicrobial agent is nanosilver, alliin and cashew nut shell liquid in a mass volume g / mL ratio of 7.5:5.8:2.5;
[0049] The thickener is xanthan gum or hydroxyethyl cellulose;
[0050] The organic silicon resin is a fluorosilicone resin;
[0051] The organic solvent is selected from ethyl acetate;
[0052] The above examples 1-3 adopt the following preparation method:
[0053] S1. Preparation of photocatalyst: Nano titanium dioxide is dispersed in anhydrous ethanol, the mass volume ratio of nano titanium dioxide to anhydrous ethanol is 20:80 g / mL, a titanium dioxide suspension is formed, a metal salt solution is added, and the mixture is stirred at a stirring speed of 2000 rpm and a temperature of 60°C for 50 min. The metal salt solution is a sodium chloride solution with a mass concentration of 65%. During the stirring process, a pulsed magnetic field oscillation is applied simultaneously, the pulsed magnetic field frequency is 10 Hz, the pulsed magnetic field voltage is 150 V, and the magnetic induction intensity is 1.8 T. The mixture is placed and calcined at 500°C for 4 h to obtain the modified nano titanium dioxide, which is the photocatalyst;
[0054] S2, preparing nano antifouling coating: stirring and mixing the photocatalyst, nano silicon dioxide, silane coupling agent, antibacterial agent, thickener, silicone resin and organic solvent to obtain nano antifouling coating;
[0055] S3, porcelain insulator substrate modification: the porcelain insulator substrate is cleaned and dried, coated with photoresist, and a desired pattern mask is formed by photolithography, and then immersed in an etchant, and immersed in an oscillation at 50° C. for 65 minutes, with an oscillation frequency of 30 KHz; the etchant includes but is not limited to hydrofluoric acid, nitric acid, hydrochloric acid or trimethylammonium hydroxide;
[0056] S4, coating: spraying the nano antifouling coating obtained in S2 onto the porcelain insulator substrate modified in S3 to obtain an antifouling porcelain insulator.
[0057] Example 4
[0058] An anti-fouling porcelain insulator comprises a mullite porcelain insulator substrate and an anti-fouling glaze layer, wherein the anti-fouling glaze layer is formed by coating an anti-fouling agent on the surface of the porcelain insulator substrate, and the coating thickness is 50 μm, and the anti-fouling agent comprises the following raw materials in parts by weight: 15 parts of nano silicon dioxide, 40 parts of photocatalyst, 3 parts of silane coupling agent, 3 parts of antibacterial agent, 5 parts of thickener, 12 parts of silicone resin, and 17 parts of organic solvent;
[0059] The photocatalyst is modified nano titanium dioxide;
[0060] The silane coupling agent is selected from KH-560;
[0061] The antimicrobial agent is nanosilver, alliin and cashew nut shell liquid in a mass volume g / mL ratio of 7.5:5.8:2.5;
[0062] The thickener is xanthan gum or hydroxyethyl cellulose;
[0063] The organic silicon resin is a fluorosilicone resin;
[0064] The organic solvent is selected from ethyl acetate;
[0065] The above-mentioned Example 4 adopts the following preparation method:
[0066] S1. Preparation of photocatalyst: Nano titanium dioxide is dispersed in anhydrous ethanol, the mass volume ratio of nano titanium dioxide to anhydrous ethanol is 15:80 g / mL, a titanium dioxide suspension is formed, a metal salt solution is added, and the mixture is stirred at a stirring speed of 1000 rpm and a temperature of 20°C for 30 min. The metal salt solution is a sodium chloride solution with a mass concentration of 50%. During the stirring process, a pulsed magnetic field oscillation is applied simultaneously, the pulsed magnetic field frequency is 8 Hz, the pulsed magnetic field voltage is 120 V, and the magnetic induction intensity is 1.2 T. The mixture is placed at 300°C and calcined for 2 h to obtain the modified nano titanium dioxide, which is the photocatalyst;
[0067] S2, preparing nano antifouling coating: stirring and mixing the photocatalyst, nano silicon dioxide, silane coupling agent, antibacterial agent, thickener, silicone resin and organic solvent to obtain nano antifouling coating;
[0068] S3, porcelain insulator substrate modification: the porcelain insulator substrate is cleaned and dried, coated with photoresist, and the desired pattern mask is formed by photolithography technology, and then immersed in an etchant, and immersed in an oscillation at 40° C. for 40 minutes, with an oscillation frequency of 25 KHz; the etchant is hydrofluoric acid;
[0069] S4, coating: brushing the nano antifouling coating obtained in S2 onto the porcelain insulator substrate modified in S3 to obtain an antifouling porcelain insulator.
[0070] Example 5
[0071] An anti-fouling porcelain insulator comprises a mullite porcelain insulator substrate and an anti-fouling glaze layer, wherein the anti-fouling glaze layer is formed by coating an anti-fouling agent on the surface of the porcelain insulator substrate, and the coating thickness is 50 μm, and the anti-fouling agent comprises the following raw materials in parts by weight: 15 parts of nano silicon dioxide, 40 parts of photocatalyst, 3 parts of silane coupling agent, 3 parts of antibacterial agent, 5 parts of thickener, 12 parts of silicone resin, and 17 parts of organic solvent;
[0072] The photocatalyst is modified nano titanium dioxide;
[0073] The silane coupling agent is selected from KH-560;
[0074] The antimicrobial agent is nanosilver, alliin and cashew nut shell liquid in a mass volume g / mL ratio of 7.5:5.8:2.5;
[0075] The thickener is xanthan gum or hydroxyethyl cellulose;
[0076] The organic silicon resin is a fluorosilicone resin;
[0077] The organic solvent is selected from ethyl acetate;
[0078] The above-mentioned Example 5 adopts the following preparation method:
[0079] S1. Preparation of photocatalyst: dispersing nano-titanium dioxide in anhydrous ethanol, with the mass volume ratio of nano-titanium dioxide to anhydrous ethanol being 25:80 g / mL, to form a titanium dioxide suspension, adding a metal salt solution, stirring at a stirring speed of 3000 rpm and a temperature of 100°C for 70 min, wherein the metal salt solution is a potassium chloride solution with a mass concentration of 80%, applying a pulsed magnetic field oscillation during the stirring process, with a pulsed magnetic field frequency of 12 Hz, a pulsed magnetic field voltage of 180 V, and a magnetic induction intensity of 2.5 T, and calcining at 800°C for 6 h to obtain the modified nano-titanium dioxide, i.e., the photocatalyst;
[0080] S2, preparing nano antifouling coating: stirring and mixing the photocatalyst, nano silicon dioxide, silane coupling agent, antibacterial agent, thickener, silicone resin and organic solvent to obtain nano antifouling coating;
[0081] S3, porcelain insulator substrate modification: the porcelain insulator substrate is cleaned and dried, coated with photoresist, and a desired pattern mask is formed by photolithography technology, and then immersed in an etchant, and immersed in an oscillation at 60° C. for 90 minutes, with an oscillation frequency of 35 KHz; the etchant includes but is not limited to hydrofluoric acid, nitric acid, hydrochloric acid or trimethylammonium hydroxide;
[0082] S4, coating: dip-coating the nano antifouling coating obtained in S2 into the porcelain insulator substrate modified in S3 to obtain an antifouling porcelain insulator.
[0083] Comparative Example 1
[0084] The difference between this comparative example and Example 3 is that the antifouling agent comprises the following raw materials in parts by weight: 25 parts of nano-silicon dioxide, 22 parts of photocatalyst, 8 parts of silane coupling agent, 10 parts of antibacterial agent, 1 part of thickener, 2 parts of silicone resin, and 10 parts of organic solvent.
[0085] Comparative Example 2
[0086] The difference between this comparative example and Example 3 is that the photocatalyst is unmodified nano titanium dioxide.
[0087] Comparative Example 3
[0088] The difference between this comparative example and Example 3 is that the antibacterial agent is nanosilver.
[0089] Comparative Example 4
[0090] The difference between this comparative example and Example 3 is that in the preparation of the photocatalyst, no pulsed magnetic field oscillation is applied during the stirring process.
[0091] Comparative Example 5
[0092] The difference between this comparative example and Example 3 is that the porcelain insulator substrate is not modified.
[0093] Test Example 1- Antifouling Performance Test
[0094] The anti-fouling performance of the porcelain insulators prepared using the above-mentioned embodiments 1-5 and comparative examples 1-5 was tested according to the following method; after coating, the porcelain insulators were flat, smooth, free of bubbles, wire drawing, and coating leakage.
[0095] 1. Hydrophobicity test: Use a contact angle meter to measure the contact angle between the insulator surface and the water droplet. Drop a drop of water on the insulator surface and use the instrument to measure the contact angle between the water droplet and the insulator surface.
[0096] 2. Artificial Simulation of Pollution Test
[0097] 1. Sample preparation: Take the porcelain insulators of the above-mentioned embodiments 1-5 and comparative examples 1-5, and ensure that the surface of the samples is clean and free of damage.
[0098] 2. Preparation of pollutants: According to the test purpose and simulated environment requirements, put 10g of sodium chloride and 20g of diatomaceous earth into a beaker, add 30mL of deionized water to prepare a pollutant solution.
[0099] 3. Apply dirt: Apply the dirt evenly on the surface of the test sample.
[0100] 4. Environmental simulation: Place the painted sample in an environment with a temperature of 35°C, a relative humidity of 90%, and a light intensity of 2000 lux.
[0101] 5. Performance test:
[0102] Flashover voltage test: Use high voltage test equipment to test the flashover voltage of the insulator. Gradually increase the voltage until the insulator flashes over, and record the flashover voltage value and flashover time. The higher the flashover voltage, the stronger the anti-pollution ability of the insulator. The longer the time from voltage application to flashover, the better the anti-pollution performance of the insulator.
[0103] Pollution flashover voltage reduction rate = (flashover voltage under clean conditions - flashover voltage under dirty conditions) /
[0104] Flashover voltage under clean conditions × 100%;
[0105] It indicates the percentage reduction of the flashover voltage of the insulator under polluted conditions relative to that under clean conditions. The lower the reduction rate, the better the anti-pollution performance.
[0106] 6. Test results
[0107]
[0108] It can be seen from the table that after the insulator samples of the embodiments were treated by the process of the present invention, the hydrophobic contact angles of the embodiments were generally high, ranging from 115° to 120°, indicating that the treated insulator surface had good hydrophobicity, which helped to reduce the adhesion of water and dirt on the surface; its flashover voltage and flashover time were improved, and the reduction rate of the pollution flashover voltage was also reduced, indicating that these treatment methods effectively improved the anti-fouling performance of the insulator. In particular, Example 3 showed excellent anti-fouling performance.
[0109] Comparing Example 3 with Comparative Example 1, the antifouling agent of the present invention can not only effectively prevent the adhesion of dirt, but also can self-clean to a certain extent, thereby reducing maintenance costs.
[0110] Compared with comparative example 2, the light absorption range of nano titanium dioxide is broadened by metal salt doping to modify the nano titanium dioxide, so that it can also have good absorption capacity in the visible light region. This enables the anti-fouling porcelain insulator to more fully utilize the visible light part of sunlight for photocatalytic reaction under natural lighting conditions, thereby improving its anti-fouling self-cleaning performance; the modified nano titanium dioxide can reduce the recombination probability of photogenerated electrons and holes. In the photocatalytic process, more photogenerated electrons and holes can participate in the redox reaction, enhancing the ability to decompose pollutants, thereby improving the anti-fouling effect of the insulator. .
[0111] Compared with comparative example 3, alliin has natural antibacterial properties, can inhibit the growth and reproduction of bacteria, and when it works in synergy with nano silver and cashew nut shell oil, it can enhance the overall antibacterial effect and reduce the drug resistance problem that may occur when a single antibacterial agent is used. Cashew nut shell oil is rich in phenolic compounds and has antioxidant and antibacterial effects. It can destroy the cell wall and cell membrane of microorganisms, interfere with the metabolic process of microorganisms, thereby inhibiting the growth of microorganisms. When used in conjunction with nano silver and alliin, it can expand the antibacterial spectrum and have a good inhibitory effect on different types of microorganisms; through the synergistic effect of the three components, the antibacterial agent can effectively inhibit the growth and reproduction of microorganisms on the surface of the anti-fouling porcelain insulator, keep the insulator clean and sanitary, and improve its anti-fouling performance and service life; the antibacterial agent cooperates with other components in the anti-fouling glaze layer, such as nano silicon dioxide, photocatalyst catalyst, etc., and the photocatalyst catalyst can produce oxidative active substances under light, and works in synergy with the antibacterial agent to further enhance the decomposition and removal ability of dirt and microorganisms, forming a glaze layer with good anti-fouling performance.
[0112] Compared with Comparative Example 4, the pulsed magnetic field can adjust the crystal form and particle size of nano-titanium dioxide and improve its photocatalytic efficiency; the pulsed magnetic field oscillation can make the nano-titanium dioxide particles more evenly dispersed in anhydrous ethanol, improve the performance consistency of the anti-fouling glaze layer, and the continuous pulsed magnetic field oscillation can reduce the precipitation of nano-titanium dioxide particles, thereby ensuring the stability of the suspension. Applying pulsed magnetic field oscillation during the stirring process can promote the full contact and uniform doping of the metal salt solution with the nano-titanium dioxide. The effect of the magnetic field can accelerate the diffusion and adsorption of metal ions on the surface of nano-titanium dioxide particles, and improve the uniformity and efficiency of doping. This helps to obtain a modified nano-titanium dioxide photocatalyst with stable performance.
[0113] Compared with Comparative Example 5, the modified porcelain insulator substrate can remove impurities such as oil and dust on the surface, so that the anti-fouling glaze layer can better contact with the substrate; the surface of the modified porcelain insulator substrate has a specific microstructure, which uses surface tension and capillary action to promote the flow of rainwater on the surface and the removal of dirt, which is conducive to the anti-fouling glaze layer to better play its anti-fouling role.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-pollution porcelain insulator, characterized in that: The invention comprises a porcelain insulator substrate and an antifouling glaze layer. The antifouling glaze layer is formed by coating an antifouling agent on the surface of the porcelain insulator substrate. The antifouling agent comprises the following raw materials in parts by weight: 10-20 parts of nano silicon dioxide, 30-50 parts of photocatalyst, 1-5 parts of silane coupling agent, 1-5 parts of antibacterial agent, 2-8 parts of thickener, 5-20 parts of organic silicon resin and 12-22 parts of organic solvent. The photocatalyst is modified nano titanium dioxide, the antibacterial agent is nano silver, alliin and cashew nut shell oil in a mass volume g / mL ratio of (5.5-9.5):(2.5-8.1):(1.2-3.8), and the thickener is xanthan gum or hydroxyethyl cellulose.
2. The anti-pollution porcelain insulator according to claim 1, characterized in that: The antifouling agent comprises the following raw materials in parts by weight: 15 parts of nano silicon dioxide, 40 parts of photocatalyst, 3 parts of silane coupling agent, 3 parts of antibacterial agent, 5 parts of thickener, 12 parts of silicone resin and 17 parts of organic solvent.
3. The anti-pollution porcelain insulator according to claim 1, characterized in that: The porcelain insulator matrix includes but is not limited to feldspar porcelain insulators, high-alumina porcelain insulators, alumina porcelain insulators, beryllium oxide porcelain insulators, mullite porcelain insulators, silicon carbide ceramic insulators or silicon nitride ceramic insulators.
4. The anti-pollution porcelain insulator according to claim 1, characterized in that: The antifouling agent is coated on the surface of the porcelain insulator substrate with a coating thickness of 40-60 μm.
5. The anti-pollution porcelain insulator according to claim 1, characterized in that: The silane coupling agent is selected from KH-560 or γ-aminopropyltriethoxysilane.
6. The anti-pollution porcelain insulator according to claim 1, characterized in that: The organic silicone resin is one or more combinations of methyl silicone resin, phenyl silicone resin and fluorosilicone resin.
7. The anti-pollution porcelain insulator according to claim 1, characterized in that: The organic solvent is selected from xylene, ethanol, isopropanol, ethyl acetate or acetone.
8. The method for preparing an anti-pollution porcelain insulator according to claim 1, characterized in that: The following steps are involved: S1. Preparation of photocatalyst: dispersing nano-titanium dioxide in anhydrous ethanol, with the mass volume ratio of nano-titanium dioxide to anhydrous ethanol being 15-25:80 g / mL, to form a titanium dioxide suspension, adding a metal salt solution, stirring at a stirring speed of 1000-3000 rpm and a temperature of 20-100°C for 30-70 min, applying a pulsed magnetic field oscillation during the stirring process, with a pulsed magnetic field frequency of 8-12 Hz, a pulsed magnetic field voltage of 120-180 V, and a magnetic induction intensity of 1.2-2.5 T, and calcining at 300-800°C for 2-6 h to obtain modified nano-titanium dioxide, i.e., a photocatalyst; S2, preparing nano antifouling coating: stirring and mixing the photocatalyst, nano silicon dioxide, silane coupling agent, antibacterial agent, thickener, silicone resin and organic solvent to obtain nano antifouling coating; S3, porcelain insulator substrate modification: the porcelain insulator substrate is cleaned and dried, coated with photoresist, and a desired pattern mask is formed by photolithography, and then immersed in an etchant, and immersed in an oscillation at 40-60° C. for 40-90 minutes, with an oscillation frequency of 25-35 KHz; the etchant includes but is not limited to hydrofluoric acid, nitric acid, hydrochloric acid or trimethylammonium hydroxide; S4, coating: coating the nano antifouling coating obtained in S2 onto the porcelain insulator substrate modified in S3 to obtain an antifouling porcelain insulator.
9. The method for preparing an anti-pollution porcelain insulator according to claim 8, characterized in that: The metal salt solution in S1 is a sodium chloride solution, a potassium chloride solution, a ferric chloride solution or a silver nitrate solution with a mass concentration of 50-80%.
10. The method for preparing an anti-pollution porcelain insulator according to claim 8, characterized in that: The coating of S4 is one of spraying, brushing or dipping.
Citation Information
Patent Citations
Preparation method of magnetic doped nano titanium dioxide
CN102794164A
Preparation method of antibacterial deodorant material based on carbon nano silver catalyst
CN104872177A
Anti-fouling polypropylene film
CN106317635A
Ceramic insulator with self-cleaning glaze and preparation method of ceramic insulator
CN113956076A
Nano-material modified wear-resistant antifouling paint and preparation method thereof
CN118359991A
Cited By
Wear-resistant antibacterial ceramic glaze as well as preparation method and application thereof
CN121135152A